2007
DOI: 10.1017/s002185960700679x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term exogenous bovine somatotropin on water metabolism and milk yield in crossbred Holstein cattle

Abstract: The present study was conducted to evaluate the effects of long-term administration of recombinant bovine somatotropin (rbST) on the regulation of body fluids, mammary blood flow (MBF) and other variables relevant to milk synthesis, in crossbred dairy cattle (0·875 of Holstein–Friesian (HF) genes and 0·125 Red Shindi (RS) genes. Ten first lactation, non-pregnant, animals were chosen and divided into the control and experimental groups of five animals each. Four consecutive measurements were carried out in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…Thermal stress, with high body temperatures or high respiratory rates, does not in itself act as an extramammary factor causing a reduction in milk production in crossbred HF animals. Other factors might be involved, since crossbred HF animals treated with bovine somatotropin under high thermal environments have been shown to increase milk yield (Chaiyabutr et al 2007b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thermal stress, with high body temperatures or high respiratory rates, does not in itself act as an extramammary factor causing a reduction in milk production in crossbred HF animals. Other factors might be involved, since crossbred HF animals treated with bovine somatotropin under high thermal environments have been shown to increase milk yield (Chaiyabutr et al 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in ECF and TBW could be an important factor influencing the process of lactation, since increases in ECF and TBW coinciding with increased milk yield in tropical crossbred HF cattle treated with bovine somatotropin have been noted (Chaiyabutr et al 2007b). However, the pattern of progressive decline in milk yield of cooled animals, despite a higher level of both ECF and plasma volume, implies that evaporative cooling does not involve a decline in mammary function as lactation advances.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the rate of blood flow to the mammary gland determines the rate of nutrient uptake by the mammary gland. During the long‐term administration of rbST in crossbred dairy cattle, it has been noted that milk yield increased with an increase in MBF in early lactation, but rbST has a less stimulating effect for milk yield as lactation advances to late lactation, despite a high level of MBF (Chaiyabutr et al . 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This proposal was indicated that humoral factors were responsible, especially the level of plasma growth hormone in the regulation of mammary circulation and milk production between 87.5%HF and 50%HF cattle. A number of studies have demonstrated that similar proportion increases in milk secretion and mammary blood flow occurred during growth hormone treatment in goats and cows (Hart et al, 1980;Chaiyabutr et al 2007). A marked decline in blood flow to the mammary gland during the transitional period from early lactation to mid-lactation in 87.5%HF cattle with the constancy of the plasma volume and blood volume were apparent (Chaiyabutr et al 2000a).…”
Section: Measurement Of Plasma Volume and Blood Volumementioning
confidence: 94%
“…Many studies have demonstrated the efficacy of bST for improvement in milk yield (Breier et al, 1991 ;Burton et al, 1994). Long term exogenous recombinant bovine somatotropin (rbST) in 87.5% crossbred Holstein cattle increased in milk yield which accompanied with an increase in the rate of mammary blood flow, but the stimulant effect for milk yield was less in late lactation despite a high level of mammary blood flow (Chaiyabutr et al 2007). It is not known which factors are the cause and which factors are the effects for such reduction.…”
Section: Other Physiological Responses In Different Stages Of Lactatimentioning
confidence: 99%